The Impact of Different Atmospheric CO2 Concentrations on Large Scale Miocene Temperature Signatures - Hossain, Akil; Knorr, Gregor; Jokat, Wilfried; Lohmann, Gerrit; Hochmuth, Katharina; Gierz, Paul; Gohl, Karsten; Stepanek, Christian; 1 Alfred Wegener Institute Helmholtz‐Centre for Polar and Marine Research Bremerhaven Germany; 4 School of Geography, Geology and the Environment University of Leicester Leicester UK (Paleoceanography and Paleoclimatology, 2023)
Based on inferences from proxy records the Miocene (23.03–5.33 Ma) was a time of amplified polar warmth compared to today. However, it remains a challenge to simulate a warm Miocene climate and pronounced polar warmth at reconstructed Miocene CO 2 concentrations. Using a state‐of‐the‐art Earth‐System‐Model, we implement a high‐resolution paleobathymetry and simulate Miocene climate at different atmospheric CO 2 concentrations. We estimate global mean surface warming of +3.1°C relative to the preindustrial at a CO 2 level of 450 ppm. An increase of atmospheric CO 2 from 280 to 450 ppm provides an individual warming of ∼1.4°C, which is as strong as all other Miocene forcing contributions combined. Substantial changes in surface albedo are vital to explain Miocene surface warming. Simulated surface temperatures fit well with proxy reconstructions at low‐ to mid‐latitudes. The high latitude cooling bias becomes less pronounced for higher atmospheric CO 2 concentrations. At such CO 2 levels simulated Miocene climate shows a reduced polar amplification, linked to a breakdown of seasonality in the Arctic Ocean. A pronounced warming in boreal fall is detected for a CO 2 increase from 280 to 450 ppm, in comparison to weaker warming for CO 2 changes from 450 to 720 ppm. Moreover, a pronounced warming in winter is detected for a CO 2 increase from 450 to 720 ppm, in contrast to a moderate summer temperature increase, which is accompanied by a strong sea‐ice concentration decline that promotes cloud formation in summer via enhanced moisture availability. As a consequence planetary albedo increases and dampens the temperature response to CO 2 forcing at a warmer Miocene background climate. Key Points: At a CO 2 level of 450 ppm, a Miocene simulation shows a global mean surface warming of +3.1°C relative to the preindustrial state. Atmospheric CO 2 increase from 280 to 450 ppm causes a warming of ∼1.4°C, which is as strong as all other forcing factors combined. At higher atmospheric CO 2 levels, the Miocene climate shows a ...